A transparent flexible z-axis sensitive multi-touch panel based on colloidal ITO nanocrystals. Issue 29 (7th July 2015) - Sangeetha, N. M.; Gauvin, M.; Decorde, N.; Delpech, F.; Fazzini, P. F.; Viallet, B.; Viau, G.; Grisolia, J.; Ressier, L.
Abstract : Resistive thin films of chemically synthesized 17 nm butanoate protected indium tin oxide nanocrystals are used to fabricate a highly transparent and flexible multi-touch panel. This panel, compatible with a stylus and a gloved/bare finger sensitively detects both the lateral position ( x, y ) of the touch and its intensity over the z -axis. Abstract : Bottom-up fabrication of a flexible multi-touch panel prototype based on transparent colloidal indium tin oxide (ITO) nanocrystal (NC) films is presented. A series of 7% Sn 4+ doped ITO NCs protected by oleate, octanoate and butanoate ligands are synthesized and characterized by a battery of techniques including, high resolution transmission electron microscopy, X-ray diffraction, 1 H, 13 C and 119 Sn nuclear magnetic resonance spectroscopy, and the related diffusion ordered spectroscopy. Electrical resistivities of transparent films of these NCs assembled on flexible polyethylene terephthalate substrates by convective self-assembly from their suspension in toluene decrease with the ligand length, from 220 × 10 3 for oleate ITO to 13 × 10 3 Ω cm for butanoate ITO NC films. A highly transparent, flexible touch panel based on a matrix of strain gauges derived from the least resistive film of 17 nm butanoate ITO NCs sensitively detects the lateral position ( x, y ) of the touch as well as its intensity over the z -axis. Being compatible with a stylus or bare/gloved finger, a larger version of this module may be readily implemented in upcoming flexible screens, enabling navigation capabilities over all three axes, a feature highly desired by the display industry.